Commercial Chinese polyherbal preparation: current status and future perspectives - Chenyao, Zhang; Haiyin, Hu; Menglong, Shi; Yucong, Ma; Fauci, Alice Josephine; Lee, Myeong Soo; Xiaolei, Wu; Junhua, Zhang; Zhaochen, Ji (Frontiers in Pharmacology, 2024)
Objective With the modernization of traditional Chinese medicine (TCM) industry, the investment in research and development of new commercial Chinese polyherbal preparations (CCPPs) is increasing, and the varieties of CCPPs are growing. CCPPs play an increasingly important role in the TCM industry. This study has comprehensively summarized and analyzed the current situation of CCPPs that has been on the market in China, and provided suggestions for the research and promotion of CCPPs. Methods This study took the CCPPs approved for marketing in domestic drug database of the National Medical Products Administration (NMPA) as the research object, and combined with the publication of related randomized controlled trials (RCTs) of CCPPs in 2020–2022 and the sales of CCPPs in domestic chain pharmacies, statistical analysis was carried out on the drug name, pharmaceutical companies, dosage form, number of flavors, CBDs, ICD-11 classification of diseases treated, etc. Results Currently, 58,409 approvals for CCPPs have been issued in China, involving 9,986 varieties of CCPPs, 2,896 pharmaceutical companies and 39 dosage forms. The number of flavors of prescriptions of CCPPs varies from 1 to 90, among which Glycyrrhiza glabra L. [Fabaceae; Glycyrrhizae radix et rhizoma] and Angelica sinensis (Oliv.) Diels [Apiaceae; Angelicae sinensis radix] are the most widely used. The study found that the CCPPs with the most diverse variety is CCPPs for the treatment of respiratory diseases, some CCPPs can treat multiple system diseases. According to the survey, the sales of CCPPs for respiratory diseases in the chain pharmacies account for more than 1/3 of the total sales of the chain pharmacies, while the number of published randomized controlled trials (RCTs) on CCPPs for circulatory diseases was the largest. Conclusion The approval process of CCPPs should be further standardized, and the transformation of TCM prescriptions into CCPPs should be promoted. In the approval process of CCPPs, it is suggested to strengthen the supervision of drug names to clarify the differences between the CCPPs of same name but different prescriptions. Improve the effectiveness and safety of CCPPs by improving the quality of CBDs. It is suggested to optimize the design of new drug research program of CCPPs to avoid waste of research resources.